Improving In Writing Descriptive Text By Using Roundtable Technique - Ybnu Taufan, Muhammad; Fatmawati (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This research is a quasi-experimental research which aims to find out whether the use of the Roundtable technique is effective in improving students' writing skills in descriptive text and to find out students' perceptions regarding the use of the Roundtable technique in improving their writing skills in descriptive text. The independent variable in this research is the application of the Roundtable technique, while the dependent variables are descriptive text writing skills and student perceptions. The population in this study was all 6 classes of Tiwikrama Mamuju Vocational School students, while the sample was class X1 as an experimental class with a total of 28 students and class X2 as a control class with a total of 28 students. The research data was obtained by giving a learning outcomes test on the descriptive text material in the form of a pre-test and post-test. The data analysis technique is by using the SPSS program, data percentages and tables. It can be concluded that the application of the Roundtable Technique has a significant effect on the writing ability of Tiwikrama Mamuju Vocational School students on the main material of description text. Apart from that, the results of the questionnaire on student perceptions are based on 4 perception assessment indicators, namely, benefits, interests, activities and implementation. The results obtained were that students predominantly gave positive perceptions of the use of the roundtable technique in improving students' writing abilities in descriptive text.